Advanced electro-optic properties of nematic liquid crystal doped with high birefringence liquid crystal molecules. (22nd November 2017) - Zhao, Yuzhen; Li, Kexuan; Ding, Siyi; Tian, Shaopeng; Ren, Huaping; Zhu, Min; Ma, Qiang; Zhao, Yang; Miao, Zongcheng
ABSTRACT: The study of fast response nematic liquid crystal display material mixture and synthesis about compounds has always been an important subject in recent years. In this article, one type of high birefringence liquid crystal based on phenyl-diacetylenes was synthesized by sonogashira coupling reaction. A research is conducted on the effect of electro-optic properties of a widely used nematic liquid crystal mixture doped with the prepared high birefringence liquid crystal molecule which concentrations ranging from 1% to 5 wt%. While the results show that the steepness of electro-optic curves first increase and then decrease with the prepared high birefringence liquid crystal molecule content increasing, when the content of high birefringence liquid crystal molecule reaches 3%, electro-optic properties of the mixture liquid crystals are excellent.